Definicja artykułu rolno-spożywczego zafałszowanego, zawarta w art. 3 pkt 10 ustawy o jakości handlowej artykułów rolno-spożywczych – wykładnia i ocena jej przydatności - Witkowski, Stanisław (Kwartalnik Prawa Publicznego, 2015)
Definition of fake agro-food article was introduced into legal system in 2008. It was adopted to differentiate offenses in food law for the ones less important (lack of concordance with rules of commercial quality) and the more important ones being a result of intentional activity of mainly producers to cheat consumers by selling them products of lower quality than they should be (fake agro-food products). Together with the adoption of the new definition the Law on Commercial Quality of Agro-food products was also supplemented with regulations providing administrative liability for marketing products not fulfilling requirements of commercial quality and fake products. The construction of the definition shows two main components – the proper definition and examples. The analysis of the proper definition demonstrate that the only element that differentiates products not fulfilling commercial activity and the fake ones is glaring violation of consumer’s interest. This makes an application of the definition very complicated as it is difficult to find a proper relationship between quality of product and consumer’s interest that would enable to distinguish between glaring and normal violation of consumer interest. The research demonstrated that the following types of consumer’s interest could be useful for the proper application of the definition – protection of consumers live and health, interest in purchasing appropriate product, interest in obtaining full and true information about product. The list is not exhaustive. Consumer’s economical interest does not belong to it as the analysis showed. Unfortunately jurisprudence was useless as there was not a single judgment found in which court would present exhaustive analysis how to distinguish between normal and glaring violation of consumer’s interest. The result of the research allowed formulating critical remarks showing far going shortcomings of the definition. Initial assumptions connected with punishing intentional faking of products were not realized as the practice of administrative liability allows imposing a penalty without any intention present. Secondly the definition appeared to be complicated for jurisprudence and in practice the opinions expressed by the judges are simply a copy of arguments used in assessed administrative decisions .